Airline Searching System - Nather, Ibrahim T. (2011)
The development of tourism industry and global economy has made flying more and more popular in people's life. While there are many flights that share the same destination and origin, their services and price varies from different airline companies. Passengers are always seeking for ticket at a low cost and services of high quality. Unfortunately, the cheap airline is tend to offer lower quality of their services, such as no beverage supplied, luggage destroy, and so on. In order to find the best choice, users always need to make a balance between the price and service offered by the airline. This project will give the users a complete assist in choosing the best airline ticket for their fly. The flight information will be stored in the database including its price, time, date, origin and destination. Besides that, the website will offer a forum for the users who had experienced this flight to discuss their experience there, so that the potential users can check the comments and have a clearer idea of the services offered by this airline. Searching for the best ticket is time consuming and troublesome, but this system solved this problem and enable users to make the wise decision efficiently. This research used the spiral methodology, and it is expected to make the airline ticketing search easier and more efficient for the customers.